ANALISIS FENOMENA PERILAKU PHUBBING DALAM INTERAKSI SOSIAL DAN AKTIVITAS AKADEMIK MAHASISWA DI KOTA MEDAN - Erwinsyah; Yummy Jumiati Marsa (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to understand the phenomenon of phubbing in one of the State Campus environments in the Pancing Area of Medan and its impact on students. Phubbing, or the act of ignoring people around because of being too focused on smartphones, is a special concern in the context of social interaction on campus. This study uses a qualitative approach with a descriptive analytical method to explore more deeply how phubbing occurs in the campus environment and how the situation affects the social, academic, and psychological lives of students. Data were collected through observation, interviews, and field documentation. The results of the study indicate that there is a Phubbing Phenomenon in the campus environment in a study conducted at one of the state campuses in the Pancing Area of Medan. The Phubbing situation affects the quality of students' social interactions, can hinder students' concentration in thinking, and has the potential to create social isolation and emotional gaps among students. This study is expected to provide insight into the development of policies and strategies to reduce the negative impacts of phubbing in the campus environment